Accessing playground safety -- design of an audit and maintenance system for the playgrounds of Worcester, Massachusetts - Wolfe, Devin Michael; Whitaker, Elizabeth Anne; Sama, David Joseph (Worcester Polytechnic Institute, 2002)
Each year about 200,000 children under the age of 15 are sent to the emergency room due to injuries that occur on the playground (Hudson 1999). Nevertheless, playground safety is currently an issue outside Federal regulation. This project seeks to minimize and/or prevent injuries on Worcester's public playgrounds. As a major toward this goal, we designed an effective safety auditing and maintenance system for the individual playgrounds in the city of Worcester that can be updated frequently and accessed easily. From these systems, we hope to make Worcester a model city in playground safety, setting the precedent for other towns and cities within the region.
Keywords: Public spaces; Public health